2019
DOI: 10.1186/s13104-019-4610-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of chronic kidney disease among adult hypertensive patients in Tigray teaching hospitals: a cross-sectional study

Abstract: Objective The aim of this study was to assess the prevalence of chronic kidney disease and to identify associated factors of chronic kidney disease among hypertensive patients. A cross-sectional study was conducted among selected 578 hypertensive patients. Data were collected using face to face interviewing questionnaires and from medical chart review. Binary logistic regression analyses were performed and analyzed using SPSS version 23.0. Result … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 15 publications
(21 reference statements)
3
19
1
Order By: Relevance
“…4 Institution-based studies in Ethiopia show that the prevalence of CKD ranges from 22.1% to 38.6%. [5][6][7] Chronic kidney disease leads to hypertension, anemia, vascular dysfunction, uremia, proteinuria, systemic inflammation, and oxidative stress that are associated with cognitive impairment. 8,9 Cognitive impairment is when a person has trouble remembering, learning new things, concentrating, or making decisions which is a common problem affecting CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 Institution-based studies in Ethiopia show that the prevalence of CKD ranges from 22.1% to 38.6%. [5][6][7] Chronic kidney disease leads to hypertension, anemia, vascular dysfunction, uremia, proteinuria, systemic inflammation, and oxidative stress that are associated with cognitive impairment. 8,9 Cognitive impairment is when a person has trouble remembering, learning new things, concentrating, or making decisions which is a common problem affecting CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis were done on 12 articles that fulfilled the inclusion criteria ( Table 1 ). A total of 3766 patients (ranging from 163 26 to 568 18 ) with chronic illnesses were involved in this study. The included studies were published from 2013 27 up to 2020 20 , 28 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although individual studies depicted age, 21 , 26 BMI, 18 , 21 , 26 and the presence of hypertension as a significantly associated factor to develop CKD. Our meta-analysis found only presence of hypertension being associated significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most (64.6%) hypertensive patients reported overweight/obesity of which 76.7% had uncontrolled hypertension, this ndings are higher than a study done in Dar-es Salaam, Tanzania where the prevalence of overweight/obesity was 67.2% and lower than a cross-sectional study in Mwanza, Tanzania which reported a prevalence of 92.2% (19,42). Overweight and obesity had 6fold increased odds for uncontrolled hypertension; Tanzania and other countries in the third world are undergoing epidemiological transition associated with urbanization and sedentary life style with increasing obesity, dyslipidemia, hypertension, diabetes, ischaemic heart disease and CKD (16,27,43,44). This discrepancy in prevalence in these studies can be attributed to differences in study populations and extent of urbanization between the cities.…”
Section: Discussionmentioning
confidence: 99%